2014
DOI: 10.3109/13880209.2014.909502
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and chemopreventive effects ofNephrolepis biserrataagainst carbon tetrachloride (CCl4)-induced oxidative stress and hepatic dysfunction in rats

Abstract: N. biserrata has strong antioxidant activities and significant protective effects against CCl4 induced hepatotoxicity in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 33 publications
13
24
0
Order By: Relevance
“…We observed that CCl 4 increased oxidative stress where it significantly increased lipid peroxidation and decreased GSH and CAT. These findings confirm previous results [35,36]. This can be explained by the metabolic activation of CCl 4 to reactive radical metabolites;CCl 3…”
Section: Discussionsupporting
confidence: 92%
“…We observed that CCl 4 increased oxidative stress where it significantly increased lipid peroxidation and decreased GSH and CAT. These findings confirm previous results [35,36]. This can be explained by the metabolic activation of CCl 4 to reactive radical metabolites;CCl 3…”
Section: Discussionsupporting
confidence: 92%
“…The potential to produce albumin proteins (which function as transport molecules) vanished in damaged hepatocytes, and the capacity to make inflammatory proteins increased. CCl 4 generated free radicals (trichloromethyl and peroxytrichloromethyl) that induced damage in hepatocytes resulting in leakage of cytoplasmic SGPT and SGOT into the bloodstream (Shah et al, 2015). Obeth ameliorated the toxic effects of CCl 4 by enhancing the activity of antioxidant molecules in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…During the phase of oxidative stress, the toxic CCl 4 metabolites lead to the depletion and dysfunction of the antioxidative defense capacities (CAT, SOD, GPx, GST, GR, and GSH) while simultaneously increasing the pro-oxidative markers (Xanthine-oxidase, NADPH oxidase, GSSG, and H 2 O 2 ), which results in oxidative stress and liver cell damage [16,35,41,42]. GSSG results from the oxidation of GSH, while NADPH oxidase transfers one electron with NADPH to O 2 , thereby generating ● O 2 ˉ [16,27].…”
Section: Discussionmentioning
confidence: 99%
“…The activity of QR was determined according to a method described by Shah et al, (2015) [35]. The reaction mixture contained of 2.06 mL of the Tris buffer (0.025 M, pH 7.4), 0.02 mL of the Tween-20 (1% w/v ), 0.1 mL of the FAD (150 μM), 0.02 mL of the NADPH (0.1 mM), 0.7 mL of the BSA (1 mg/mL), 0.05 mL of liver homogenate (10%), and 0.05 mL of the 2,6-dichlorophenolindophenol (2.4 mM).…”
Section: Methodsmentioning
confidence: 99%